Cancer neptuni Linnaeus, 1768 (now Alima neptuni): original description, authorship and date of publication (Crustacea: Stomatopoda: Squillidae) - Low, Martyn E. Y.; Ahyong, Shane T. (Zootaxa, 2017)
The original description of the stomatopod species Cancer neptuni (currently known as Alima neptuni) has been accepted as being published in the third volume of the twelfth edition of the Systema naturae by Linnaeus (1768a: 226) by virtually all authors (e.g., Manning & Lewinsohn 1986: 13; Holthuis 2000: 17, 18; Ahyong 2001: 188; Ahyong 2002: 362; Ahyong 2005: 206; Lucatelli et al. 2012: 282). Linnaeus (1768a) is known to have been published after 28 January 1768 because a publication of that date is cited in the Prefatio of that work (p. [3], footnote).